Actinomycin D upregulates proapoptotic protein Puma and downregulates Bcl-2 mRNA in normal peripheral blood lymphocytes - Kalousek, Ivan; Brodska, Barbora; Otevrelova, Petra; Röselova, Pavla (Anti-cancer drugs, 2007)
We have examined the ability of actinomycin D to induce apoptosis in human peripheral blood lymphocytes. Run-On assays were performed to specify the primary molecular damage, reverse transcription-PCR, Western blots and flow cytometry studies were performed to ascertain which proteins of the apoptosis machinery were affected to cause actinomycin D-induced cell death. Expression of 23 apoptosis-related genes was investigated. The down-regulation of ribosomal RNA synthesis caused by actinomycin D induced a mitochondria-dependent apoptosis. Although the expression of the majority of examined genes remained indifferent against actinomycin D activity, the cellular level of p53 protein increased, subsequently upregulating both Puma mRNA and protein. Puma-mediated mitochondrial apoptosis was accompanied by nucleolin cleavage and Bcl-2 mRNA destabilization. The stability of the cellular level of Bcl-2 protein independent of a mRNA decrease suggests that protection of Bcl-2 protein against proteasomal degradation can moderate the apoptotic process. In peripheral blood lymphocytes cultured in vitro, the apoptosis induced by a low concentration of actinomycin D (10 nmol/l) is dependent on p53 and Puma activation. This apoptotic pathway is demonstrated in peripheral blood lymphocytes for the first time. A different apoptotic pathway induced in peripheral blood lymphocytes using this drug has, however, been previously revealed by other authors. The combination of cell specificity and dose-dependent effects can likely play a decisive role in apoptosis observed in peripheral blood lymphocytes after genotoxic drug application.
Keywords: nádorový supresorový protein p53; messenger RNA; Dose-Response Relationship, Drug; DNA Damage; vztah mezi dávkou a účinkem léčiva; Up-Regulation; apoptóza; průtoková cytometrie; mitochondrie; Lymphocytes; upregulace; lidé; poškození DNA; down regulace; Proto-Oncogene Proteins; lymfocyty; Tumor Suppressor Protein p53; DNA, Ribosomal; Down-Regulation; western blotting; daktinomycin; polymerázová řetězová reakce s reverzní transkripcí; Flow Cytometry; Blotting, Western; RNA, Messenger; Apoptosis Regulatory Proteins; Humans; Proto-Oncogene Proteins c-bcl-2; Antibiotics, Antineoplastic; Dactinomycin; ribozomální DNA; viabilita buněk; protoonkogenní proteiny; Cell Survival; Mitochondria; Reverse Transcriptase Polymerase Chain Reaction; proteiny regulující apoptózu; protinádorová antibiotika; protoonkogenní proteiny c-bcl-2; Apoptosis